Long-Term Treatment with Apixaban in Patients with Atrial Fibrillation: Outcomes during the Open-Label Extension following AVERROES - Benz, Alexander P.; Eikelboom, John W.; Yusuf, Salim; Hohnloser, Stefan H.; Kahl, Anja; Beresh, Heather; Balasubramanian, Kumar; Healey, Jeff S.; Connolly, Stuart J. (Thrombosis and Haemostasis, 2020)
Background AVERROES, a randomized controlled trial in high-risk patients with atrial fibrillation, unsuitable for vitamin K antagonist therapy, demonstrated efficacy and safety of apixaban compared with aspirin. At the conclusion of the double-blind phase, an open-label extension was initiated to allow study participants to receive apixaban until it became locally available. This study reports outcomes of patients on apixaban during the open-label extension.Methods Rates of stroke or systemic embolism, hemorrhagic stroke, major bleeding, and other outcomes during the open-label extension are reported.Results Of the 5,599 participants enrolled in AVERROES, 3,275 (58.5%) received apixaban during the open-label extension. Median (interquartile range) follow-up in the open-label extension was 3.0 (2.5–3.5) years. The rate of stroke or systemic embolism during the open-label extension was 1.0% per year, and the annual rates of hemorrhagic stroke and major bleeding were 0.3 and 1.2%, respectively. After adjustment for imbalances in patient variables, event rates in patients on apixaban during the open-label extension were similar to those of patients receiving apixaban during AVERROES. Additional analyses in all patients who received apixaban, at any time from the start of AVERROES to the end of the open-label extension, were performed. This cohort (n = 4,414) showed annual event rates of 1.1% for stroke or systemic embolism, 0.3% for hemorrhagic stroke, and 1.2% for major bleeding.Conclusion During the open-label extension, annual rates of stroke or systemic embolism, hemorrhagic stroke, and major bleeding remained as low as those observed during apixaban treatment in AVERROES. These data support the long-term efficacy and safety of apixaban in patients with atrial fibrillation.
Keywords: apixaban; extension; atrial fibrillation; stroke; bleeding